Penyidikan Tindak Pidana Peredaran Kosmetik Palsu Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Oleh Direktorat Reserse Kriminal Khusus Kepolisian Daerah Riau - Ridwan Sahputra; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Along with the era of free trade now various types of cosmetics in the market with various uses of various brands as well. Cosmetic products that are the result of development of the pharmaceutical industry has now developed into one of basic needs of the community along with the development of people’s lifestyles. Business players are competing to produce various kind of beauty products with various uses for the community to attract consumers as much as possible. The human desire to always look beautiful, perfect in all opportunities untilized by a group of business actors who are not responsible for producing or trading cosmetics that do not meet the requirements to the public. The main target is the woman who want to get quick and maximum result.Based on the description, the authors are interested to conduct research under the title criminal investigation of counterfeit cosmetics based on law Number 8 0f 1999 on Costumer protection by the special criminal investigation Directorate of Riau Regional Police, while the purpose of this study is to determine the cause of circulatory factors fake cosmetics in the jurisdiction of the special criminal investigation Directorate of Polda Riau, then the last know to process of investigation of fake cosmetics crime by the Directorate of special Criminal investigation Polda Riau.In the study of authors use descriptive research that aims to describe precisely the properties of an individual, circumstances, symptoms or a particular group, or to determine the translation of a symptom, or to determine whether there is a relationship between a symptom with other symptoms in society. The study provides an illustration of the rampant circulation of fake cosmetics in the justification of the Riau Police as well as the impact raised and how to follow up the case.